Food security and nutrition - Flores Céspedes, José (2019)
In this article, a review is made of different documents of the FAO Organization of the United Nations which addresses food security and education for nutrition focused on the world, Latin America and especially our country.Also, it studies the proposal for changes and schemes to improve food security and nutrition by the United Nations. In this part, it shows the works and advances product of the effort of the Peruvian State to give an orientation and criteria of solution to the problematic generated in these subjects.Finally, it is analyzed how ethics becomes present in the problem of food security and nutrition from the approach of diverse actors, and what actions and positions based on ethics should be the most suitable in a reality related to these issues that do not It stops being very complex.